The Influence of Perceptions of Ease, Usefulness, Risk, Trust, and Religiosity on Financing Decisions in Sharia Peer-To-Peer Lending - Zakiyyati, Qurrota A'yun; Marhadyta, Ajrina Valentine; Hakam, Abdul; Kinanti, Risma Ayu (Majapahit Journal of Islamic Finance and Management, 2025)
Sharia-based peer-to-peer (P2P) lending has emerged as an alternative for individuals seeking online financing aligned with Islamic principles. Despite the rapid growth of financial technology in Indonesia, the market share of Sharia P2P lending remains significantly lower than that of conventional platforms. This study aims to examine the influence of perceived ease of use, perceived usefulness, risk, trust, and religiosity on financing decisions in Sharia P2P lending. A quantitative method with a causal design was employed, involving 100 respondents selected through purposive sampling. Primary data were gathered via online questionnaires and analyzed using multiple linear regression with SPSS version 22. The results indicate that perceived usefulness has a positive and significant effect on financing decisions. In contrast, perceived ease of use, risk, trust, and religiosity do not have a significant partial effect. However, all variables collectively exert a positive and significant influence on financing decisions. These findings highlight the importance of enhancing users’ perceptions of usefulness and addressing perceived risks to increase the adoption of Sharia-compliant digital financial services.